MONITORING TINGKAT KEBERSIHAN SEPTIC TANK BERBASIS INTERNET OF THINGS (IoT) - Zuhal Mujaddid samas; Antamil Antamil (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2021)
Domestic blackwater sewage is usually placed in a reservoir called a septic tank. Black water type waste water is channeled to the residents' septic tanks, but there are still many people who have septic tanks that do not meet the established standards so it impacts the need for a hygiene assessment at every certain period. Apart from that, fecal sludge accumulation in the septic tank can store various contents, one of which is methane gas or CH4 which can explode and endanger the septic tank cleaning workers. This type of research is quantitative with an experimental approach. The design of tool design uses a prototype model. In this study, two types of sensors were used, namely the MQ-4 sensor and the HC-SR04 sensor. The results of this study are in the form of a methane gas detector and a height measuring device, to determine whether the septic tank has high or low methane levels in the form of a percentage in the serial monitor, and also becomes a reference for when the septic tank is full which is marked notification on the application. Blynk uses NodeMCU so that it can know the time of the septic tank desludging process.